Dialog Sebagai Cara Hidup Menggereja di Kultur Indonesia - Yusuf Siswantara (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2020)
Dialogue is not a mere empty term or theory; it is evident in religious life and even becomes a necessity in the attitude of participation as a knot of kenosis thought (A. Pieris) and Asian theology (C.S. Song). The ideal dialogue model has been narrated in the story of Emmaus' journey which also became a model of the Lord's Supper. Thus, the ideal of dialogue is the story of the Eucharist. Indonesia as part of Asia has its own diversity context. The method in this article is qualitative, using the method of analyzing literature from various figures' thoughts about the dialogue that can be applied in the Indonesian context. As a result, there are four forms of dialogue that can be applied in the context of Indonesia's diversity, by specializing in a dialogue of work and dialogue of life. Abstrak: Dialog bukanlah istilah kosong atau teori belaka; kata ini nyata dalam kehidupan beragama dan, bahkan, menjadi keharusan dalam sikap partisipasi sebagai simpul pemikiran kenosis (A. Pieris) dan teologi Asia (C.S. Song). Model dialog ideal telah dinarasikan dalam kisah perjalanan Emaus yang juga menjadi model perjamuan kudus. Dengan demikian, idealitas dialog adalah kisah perjamuan kudus. Indonesia sebagai bagian dari Asia memiliki konteks keberagamannya sendiri. Metode dalam artikel ini adalah kualitatif, dengan menggunakan metode analisis literatur dari berbagai pemikiran tokoh tentang dialog yang dapat diterapkan dalam konteks Indonesia. Hasilnya, ada empat bentuk dialog yang bisa diterapkan dalam konteks keberagaman Indonesia, dengan mengkhususkan dialog karya dan dialog kehidupan.